2021
DOI: 10.1038/s41598-021-92480-w
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the substrate binding mechanism of SULT1A1 through molecular dynamics with excited normal modes simulations

Abstract: Sulfotransferases (SULTs) are phase II drug-metabolizing enzymes catalyzing the sulfoconjugation from the co-factor 3′-phosphoadenosine 5′-phosphosulfate (PAPS) to a substrate. It has been previously suggested that a considerable shift of SULT structure caused by PAPS binding could control the capability of SULT to bind large substrates. We employed molecular dynamics (MD) simulations and the recently developed approach of MD with excited normal modes (MDeNM) to elucidate molecular mechanisms guiding the recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 58 publications
2
22
0
Order By: Relevance
“…Each excitation step is followed by a relaxation time. In line with other studies, we found that excitation energies of 2-3 K coupled with relaxation times ranging from 4 to 8 ps (Costa et al, 2015;Floquet et al, 2015;Dudas et al, 2020Dudas et al, , 2021aDudas et al, , 2021b) are broadly applicable. The number of cycles varies by system (Table 2).…”
Section: With Excited Normal Modessupporting
confidence: 92%
See 1 more Smart Citation
“…Each excitation step is followed by a relaxation time. In line with other studies, we found that excitation energies of 2-3 K coupled with relaxation times ranging from 4 to 8 ps (Costa et al, 2015;Floquet et al, 2015;Dudas et al, 2020Dudas et al, , 2021aDudas et al, , 2021b) are broadly applicable. The number of cycles varies by system (Table 2).…”
Section: With Excited Normal Modessupporting
confidence: 92%
“…Even though NMs are usually computed in vacuum, they are used as privileged directions in MD simulations with an explicit representation of the surrounding medium. MDeNM has demonstrated its power in conformational sampling in several studies revealing important protein functional movements (Dudas et al, 2020;Dudas et al, 2021a;Fagnen et al, 2020;Fagnen et al, 2021) and has also been successfully used in ensemble docking studies (Dudas et al, 2021b). CoMD provides a combination of ENM-NMA and targeted MD, coupled with energy minimization to adaptively generate a series of conformers.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the docking into the MD conformations allowed for the improvement of the Alpha HB and LondondG docking scores of sub-cluster 7.2, underlying the importance of taking into account the conformational changes of SULTs when exploring interactions with their ligands. Our recent study [25], using MD simulations with excited Normal Modes (MDeNM) [68], demonstrated that the natural flexibility of SULT1A1 provides a large opening of the key loops 1, 2, and 3, thus ensuring the recognition of diverse substrates and inhibitors by SULT1A1, the large inhibitor epigallocatechin gallate, in particular [20].…”
Section: Docking Resultsmentioning
confidence: 99%
“…SULTs metabolize a wide variety of substrates, including endogenous compounds like steroids and polysaccharides, natural compounds [12,13] and drugs [8]. The molecular mechanisms involved in the substrate specificity of different SULT isoforms have been previously studied [14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…While it is not possible to review all reports here, appreciate that the study of SULT kinetics has generated an array of models. Steady state kinetic studies of various SULTs have yielded both sequential ordered [15,[20][21][22][23] and random [24][25][26][27][28] mechanisms. Isotope exchange at equilibrium was thought to prove an ordered mechanism [29], but this has been criticized as overlooking the formation of dead end complexes within a random scheme [30].…”
Section: Introductionmentioning
confidence: 99%